STEGANOGRAFI DENGAN METODE PENGGANTIAN LEAST SIGNIFICANT BIT (LSB) (Jurnal Pilar Sains, 2007)
Steganography is the art and science of writing hidden messages in such a way that no one, apartfrom the sender and intended recipient, suspects the existence of the message. Least Significant Bit method (LSB) is one of steganography method to hiding data by changing bit LSB in segment of image with secretdata bit. The changing image can be applied without humanly visible degradationKeywords : Image, Least Significant Bit,, Steganography, degradation.